2007
DOI: 10.1002/pssb.200674716
|View full text |Cite
|
Sign up to set email alerts
|

Structural transition control of laterally overgrown c‐GaN and h‐GaN on stripe‐patterned GaAs (001) substrates by MOVPE

Abstract: Growth mechanisms and material quality of the laterally overgrown cubic-phase gallium nitride (c-GaN) and hexagonal-phase gallium nitride (h-GaN) on stripe-patterned GaAs (001) substrates were investigated using transmission electron microscopy (TEM). Investigational results show that h-GaN is only laterally overgrown along the (111)B facets of the c-GaN stripes with the growth direction of (0001) , which is six orders of magnitude smaller than that in the conventionally grown h-GaN films. On the other hand, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…3, respectively. Both of the patterns represent the features of the zincblende structure [10,11]. Diffraction spots from c-GaN around the dot are slightly overlapped to the pattern of the c-InN dot in Fig.…”
Section: Contributed Articlementioning
confidence: 87%
See 1 more Smart Citation
“…3, respectively. Both of the patterns represent the features of the zincblende structure [10,11]. Diffraction spots from c-GaN around the dot are slightly overlapped to the pattern of the c-InN dot in Fig.…”
Section: Contributed Articlementioning
confidence: 87%
“…Before deposition, a MgO substrate was thermally cleaned for 30 minutes at 1100 o C to obtain an atomically flat surface. Then a 15 nm-thick low temperature (LT) GaN buffer layer was grown on the substrate at 550 o C followed by the growth of a c-GaN underlayer with a thickness of 500 nm at 800 [10,11], and was kept throughout the following processes of the GaN cap growth and second InN deposition. Figure 2 shows AFM images taken after each fabrication step of the stacking structure.…”
Section: Methodsmentioning
confidence: 99%
“…The islands exhibit lateral facets that are inclined by $101 with respect to the growth direction and additional facets on the top which are inclined by $ 201 with respect to the sample template surface. Sanorpim et al [15] have observed similar faceting of cubic GaN in their studies of epitaxial lateral overgrowth of (0 0 1)-oriented stripe-patterned GaAs with cubic GaN by MOVPE. The mechanism of facet formation is not completely understood yet and will be a topic of further studies.…”
Section: Resultsmentioning
confidence: 72%
“…The tilted angles between GaAs (002) plane and cubic (002) and hexagonal (10)(11) planes in the InN layers are 0° and ±7°, respectively. This demonstrates that the hexagonal-phase presented in the c-InN layers is mainly constructed on the cubic (111) surfaces and the crystal orientation relationship between hexagonal-phase inclusion and c-InN is hexagonal (0001)//cubic (111) [12,13].…”
mentioning
confidence: 92%